A novel immune signature predicts immunotherapy responsiveness and reveals the landscape of the tumor immune microenvironment in head and neck squamous cell carcinoma - Wang, Qiwei; Zhao, Yinan; Wang, Fang; Tan, Guolin (Frontiers in Genetics, 2022)
Background Immune-checkpoint blockade (ICB) has been routinely implemented to treat head and neck squamous cell carcinoma (HNSCC) patients. However, there are only a few patients benefit from immune checkpoint inhibitors (ICIs) therapies. Methods In this study, we used a combined cohort (including the GSE41613, GSE65858, TCGA and CELL cohorts) to identify hub genes significantly associated with ICB and activated CD8+ T-cell gene signatures. We performed the single‐sample gene set enrichment analysis (ssGSEA) to quantify the expression of hub genes and constructed a novel immune signature named the IMS that predicts the immunotherapy responsiveness, prognosis, immune infiltration, and clinical characteristics. Data from the GSE102349 external cohort and the pembrolizumab cohort obtained from a clinical trial were used to validate the efficiency of the IMS. In addition, we revealed potential mechanisms of the antitumour response by analysing the HNSCC single-cell database. Finally, we used the LASSO algorithm to build an IMS-related risk model. Results The high IMS group was associated with significant immune activation, better prognosis, and increased immunotherapy responsiveness; thus, the IMS potentially represents a candidate biomarker for ICB. Moreover, a tumour microenvironment with a higher IMS underwent remarkable metabolic reprogramming characterized by enrichment in the glycolysis/gluconeogenesis, oxidative phosphorylation, and citrate cycle (TCA cycle) pathways. We also revealed insightful information on cellular crosstalk between the IMS and other immune lineages, which may mechanistically explain immune escape. In addition, we constructed and validated a risk prediction model (CD2, TBC1D10C and CD3E) that could stratify HNSCC patients based on survival and response to ICB treatment Conclusions IMS is a signature closely correlated with the tumour immune microenvironment. The findings of this study contribute to the understanding of the immune landscape in HNSCC patients. IMS may aid in the clinical management of HNSCC patients through the identification of effective immunotherapies for specific patients.